ASPEK SYARIAH PADA INSTRUMEN SUKUK: ANALISIS PENERAPAN SUKUK WAKAF DI INDONESIA - Muhayatsyah, Ali (J-ISCAN: Journal of Islamic Accounting Research., 2020)
Sukuk is a letter of acknowledgment of cooperation which has a more diverse scope than just an acknowledgment of debt. The sukuk transaction is not a debt contract, but rather participation. Sukuk issuance is issued with an underlying asset. Sukuk issuance must first obtain a statement of compliance with sharia principles to convince investors that the sukuk has been structured according to sharia. The parties involved in the issuance of the sukuk are Obligors, Special Purpose Vehicle (SPV), Investors. The income received by investors can be in the form of profit sharing, fees and certain margins. When due, the principal of the loan will also be returned to the holder. Issuers act as fund managers and investors act as owners of capital. The profit obtained by investors is a proportional share of the profits from the management of funds by investors. The issuance of sukuk linked waqf involves several parties, at least consisting of the Indonesian Waqf Board (BWI), state-owned companies, SPV, and investors. Waqf sukuk in Indonesia can be issued by private companies or state-owned companies. The sukuk mechanism is carried out by leasing the waqf assets to the sukuk issuer. The sukuk issuer will then issue the sukuk to investors. After the money from investors comes in, the sukuk issuer will contact the contractor to build assets on the waqf land. Then the asset is leased to a third party. The rent is paid to the sukuk issuer, then paid to the nazir. At the end of the period the waqf asset becomes the property of the nazir, returns to the nazir. Land and buildings, administered by the nazir. Keywords: Islamic Bond, Sukuk Linked Wakaf, Sukuk Ijarah, Sukuk Mudharabah. Abstrak Sukuk merupakan surat pengakuan kerjsama yang memiliki ruang lingkup yang lebih beragam dibandingkan hanya sekedar surat pengakuan hutang. Transaksi sukuk bukan akad utang piutang melainkan penyertaan. Penerbitan sukuk diterbitkan dengan suatu underlying asset. Penerbitan sukuk harus terlebih dahulu mendapatkan pernyataan kesesuaian prinsip syariah untuk meyakinkan investor bahwa sukuk telah distruktur sesuai syariah. Pihak-pihak yang terlibat dalam penerbitan sukuk adalah Obligor, Special Purpose Vehicle (SPV), Investor. Penghasilan yang diterima investor bisa berupa bagi hasil, fee, dan margin tertentu. Ketika jatuh tempo, pokok pinjaman juga akan dikembalikan kepada pemegangnya. Emiten bertindak selaku pengelola dana dan investor bertindak selaku pemilik modal. Keuntungan yang diperoleh investor merupakan bagian proporsional keuntungan dari pengelolaan dana oleh investor. Penerbitan sukuk linked wakaf melibatkan beberapa pihak, setidaknya terdiri dari Badan Wakaf Indonesia (BWI), Perusahaan BUMN, SPV, dan investor. Sukuk wakaf di Indonesia dapat diterbitkan oleh perusahaan swasta ataupun BUMN. Mekanisme sukuk ini dilakukan dengan menyewakan aset wakaf kepada penerbit sukuk. Penerbit sukuk kemudian akan menerbitkan sukuk kepada investor. Setelah uang dari investor masuk, penerbit sukuk akan menghubungi kontraktor untuk dibangun aset di atas tanah wakaf. Kemudian aset tersebut disewakan ke pihak ketiga. Uang sewa dibayar ke penerbit sukuk, kemudian dibayar juga ke nazir. Pada akhir periode aset wakaf tadi menjadi milik nazir, kembali ke nazir. Tanah dan bangunan, dikelola oleh nazir. Kata kunci: Obligasi Syariah, Sukuk Linked Wakaf, Sukuk Ijarah, Sukuk Mudharabah